The molecular physiology of liver regeneration following partial hepatectomy - Mangnall, David; Bird, Nigel C; Majeed, Ali W. (Liver international, 2003)
: The ability of the liver to regenerate after resection has been known for many years. Two reports from Germany in the late 1800s probably mark the introduction of the phenomenon into the scientific literature, but in the early 1900s the first reviews of this subject had appeared in the English literature. Predating these early scientific reports the legends from the Greek mythology described the fate of Prometheus. As punishment for defying Zeus and revealing the secret of fire to man, Prometheus was chained to a rock and each day had part of his liver ripped out by an eagle which, returning the following day, repeated the torture because his liver regenerated itself overnight. Although the speed of regeneration in the Greek legend is somewhat greater than that observed either clinically or in the laboratory, the myth does serve to emphasise the remarkable ability of the liver to repeatedly regenerate following repeated resections. This review aims to summarise the more recent literature concerning the early molecular events accompanying liver regeneration and to integrate this with the existing knowledge of this subject.